2014
DOI: 10.1177/0888406414538843
|View full text |Cite
|
Sign up to set email alerts
|

New Literacy Studies

Abstract: Even as research continues to suggest the potential of assistive technology for improving student outcomes, it remains under-utilized in schools. Among numerous challenges to the effective utilization of assistive technology, research has suggested that educators are inadequately prepared to consider and implement the use of such technologies. In this article, we complement the effort to delineate the competencies needed by teachers for this purpose by suggesting that New Literacy Studies can serve as a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…New technologies and media have been viewed as a means for inclusive pedagogy. Historically, technological and information devices for students with LD were seen as assistive technologies to help bridge the gap in their challenges with print or other skillsets (Naraian & Surabian, 2014). Now however, new technologies have been positioned as tools that promoted independence, participation, and motivation for more positive learning experiences beyond "normative skill expectations" for students with LD (Blackhurst, 2005;Bruce et al, 2013;Laidlaw & O'Mara, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…New technologies and media have been viewed as a means for inclusive pedagogy. Historically, technological and information devices for students with LD were seen as assistive technologies to help bridge the gap in their challenges with print or other skillsets (Naraian & Surabian, 2014). Now however, new technologies have been positioned as tools that promoted independence, participation, and motivation for more positive learning experiences beyond "normative skill expectations" for students with LD (Blackhurst, 2005;Bruce et al, 2013;Laidlaw & O'Mara, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of digital technology is a breakthrough in education because it offers a solution to limitations in time, place and funding in the implementation of the learning process (Koç, 2017;Strobl et al, 2019;Davey, Elliott & Bora, 2019;Boyle & Kennedy, 2019;Cheng & Lai, 2019;Shaikh, 2019). However, before its application, teachers require procedural assistance and preparation (Lall et al, 2019;Naraian & Surabian, 2014). Wu, Corr & Rau (2019) suggest that students make many mistakes in understanding learning materials due to different representations.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…Teachers often believe that AT is complicated, hard to use, and can be implemented by only a few trained professionals; they also lack confidence in their use of AT (Connor & Beard, 2015;Dissinger, 2003;O'Sullivan et al, 2021). Previous research (Atanga et al, 2020;Naraian & Surabian, 2014;Schaaf, 2018) indicated that teachers' limited AT competencies are primarily due to insufficient training. It is not feasible for teachers to implement AT effectively and meaningfully without receiving specific training and support.…”
mentioning
confidence: 99%